2018
DOI: 10.1177/1464420718789447
|View full text |Cite
|
Sign up to set email alerts
|

Dissimilar friction-stir welding of 430 stainless steel and 6061 aluminum alloy: Microstructure and mechanical properties of the joints

Abstract: The effect of friction-stir welding parameters on the microstructure and the mechanical properties of the dissimilar 430 stainless steel and 6061 aluminum alloy joints were investigated. Optical and scanning electron microscopes in conjunction with energy dispersive X-ray analysis were employed to study the microstructure of the joints. Tensile and microhardness tests were used to evaluate the mechanical properties. The results showed that the best appearance quality was achieved at a rotational speed of 900 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 26 publications
(42 reference statements)
1
14
0
Order By: Relevance
“…This is consistent with the obtained tensile strength values. The bimodal behavior was reported by Zandsalimi et al [45] when investigating the dissimilar FSW of 430 stainless steel and 6061 aluminum alloy. These showed that this bimodal fracture occurs in the aluminum HAZ, which has the lowest hardness.…”
Section: Mechanical Propertiessupporting
confidence: 64%
“…This is consistent with the obtained tensile strength values. The bimodal behavior was reported by Zandsalimi et al [45] when investigating the dissimilar FSW of 430 stainless steel and 6061 aluminum alloy. These showed that this bimodal fracture occurs in the aluminum HAZ, which has the lowest hardness.…”
Section: Mechanical Propertiessupporting
confidence: 64%
“…Sumit et al [66] reported that during FSP on aluminum, high heat inputs cause over plasticization and formation of groove defects. Zand Salimi [67] also indicated that grooves form during FSW of AA6061 and 430 stainless steel, because high input produces a plasticized material in the SZ which cannot be maintained by the tool shoulder. On the other hand, the grooves (type 2) form due to insufficient stirring.…”
Section: The Mechanism Of Groove Formationmentioning
confidence: 99%
“…A common ground to these studies is that the excessive heat input and temperature in welds caused by high rotational speed and low welding speed favor the formation of thick IMC layers. This is because the tool causes high friction with the workpiece per unit time, thereby increasing temperature and hence the number of IMCs [46]. Wan et al [13] investigated the effect of rotational speed and welding speed on microstructure and mechanical properties of FSW joints between AA6082-T6 and Q235A steel.…”
Section: Rotational Speedmentioning
confidence: 99%
“…Upon applying pressure by tool shoulder, plasticized materials tend to come out of the weld seam like flash, leaving behind a groove on top of the weld surface. Zandsalimi et al [46] found that, in FSW of AA6061 and 430 stainless steel, tool shoulder was not able to contain the plasticized material inside the weld seam, as too high heat input was involved (rotational speed of 900 rpm and welding speed of 40 mm/min). As a result, macroscopic flash and grooves appeared on the weld surface, as displayed in Figure 20.…”
Section: Surface Grooves and Flash Generationmentioning
confidence: 99%
See 1 more Smart Citation